OA−ICOS−Based Oxygen and Carbon Dioxide Sensors for Field Applications in Gas Reflux Chicken Coops - Weijia Li; Guanyu Lin; Jianing Wang; Jifeng Li; Yulai Sun; Depu Yao; Xiaogang Yan; Zhibin Ban (Sensors)
To facilitate the effective assessment of respiratory entropy during poultry breeding, a novel oxygen (O2) and carbon dioxide (CO2) sensor was developed based on the off−axis integrated cavity output spectroscopy technique, featuring effective absorption optical paths of 15.5 m and 8.5 m, respectively. The sensor employs integrated environmental control technology, substantially enhancing detection precision. To improve the instrument’s response speed, the miniaturization of the cavity and structural optimization were implemented, achieving a rapid response time of merely 6.22 s, addressing the stringent requirements for quick responsiveness in poultry respiration thermometry research. A signal processing model tailored for on−site applications was designed, boosting the system’s signal−to−noise ratio by 4.7 times under complex environmental noise conditions. Utilizing Allan variance analysis, the sensor’s detection limits for O2 and CO2 were ascertained to be 2.9 ppm and 7.4 ppb, respectively. A 24−h field application test conducted in Gongzhuling demonstrated that the sensor’s results align with the respiratory characteristics of poultry under normal physiological conditions, validating its extensive potential for application in respiratory analysis, environmental monitoring, and industrial sectors.